Greve do voto: a política da antipolítica nas eleições municipais de 2004 em Fortaleza - Bezerra, Glícia Maria Pontes (2010)
This study discusses the use of communication strategies in the dispute for political hegemony in the contemporary society. In order to do so, one starts from the concept of politics in its broad sense, involving, besides parties and parliaments, the groups and organized social movements. The comprehension that the political activity, nowadays, involves the media, made part of this study be focused on the investigation of problems in this relationship. We analyzed, especially, the communication actions promoted by the Grupo Crítica Radical, in which participate, among others, Maria Luiza Fontenelle, former mayor of Fortaleza, and Rosa da Fonseca, former concillor. They left their old parties after a process of self-criticism concerning their incumbencies, partly influenced by the books of Robert Kurz about the collapse of capitalism . After this historical contextualization, one starts the analysis of the campaign Greve do Voto promoted by the Group during the municipal elections of 2004. The production of campaign material, the street drama, the small shows and the fact that the press covered the campaign are discussed starting from the theoretical formulations presented on this research, understanding, this way, the challenge of these groups to build an action against the hegemony allied to the universe of the mass media